Penanganan Surat Masuk dan Surat Keluar di Subbagian Tata Usaha dan Arsip Bagian Umum Sekretariat Daerah Kota Pariaman - Elita, Elita; Nst., Bakhtaruddin (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of this research are describing: 1) to enter and go out mail handling procedures at Subbagian Tata Usaha dan Arsip Bagian Umum Sekretariat Daerah Kota Pariaman, 2) to enter and go out mail handling obstruction at Subbagian Tata Usaha dan Arsip Bagian Umum Sekretariat Daerah Kota Pariaman. The data were collected through observation, interview, and document study. The conclude is: First, to enter mail handling procedures at Subbagian Tata Usaha dan Arsip Bagian Umum Sekretariat Daerah Kota Pariaman including: reception, registration, to convey, and process. To go out mail handling procedures at Subbagian Tata Usaha dan Arsip Bagian Umum Sekretariat Daerah Kota Pariaman including: to make mail concept, to type, to sign, to register, to copy, and to send. Second, obstruction from enter and go out mail handling at Subbagian Tata Usaha dan Arsip Bagian Umum Sekretariat Daerah Kota Pariaman that is work less from official, still few equipment and manual system of archives. Keyword: mail handling; procedures